Marketing sensorial relacionado al comportamiento de compra del consumidor en restaurantes turísticos de Iquitos 2022 - Perez Garcia, Alberto Geraldino (2025)
The purpose was to determine the relationship between sensory marketing and consumer purchasing behavior in tourist restaurants, Iquitos 2022. This was a quantitative, non-experimental, descriptive, cross-sectional and correlational study; The population was made up of 88 consumers who visit tourist restaurants. The survey was used as a technique and instrument, the Likert Scale (validity of 82%, reliability 83.3%). The results were: sensory marketing of the consumer, rated as high 63.6% (56) and medium 36.4% (32), according to dimensions: visual, high 63.6% (56), medium 34.1% (30) and low 2.3% (2); olfactory, high 52.3% (46), medium 43.2% (38) and 4.5% (4) low; auditory, high 63.6% (56), medium 35.2% (31) and low 1.1% (1); gustatory, medium 61.4% (54), high 34.1% (30) and low 4.5% (4); tactile, medium 64.8% (57), high 31.8% (28) and low 3.4% (3). The consumer's purchasing behavior in tourist restaurants was rated 59.1% (52) medium, 39.8% (35) high and 1.1% (1) low; according to dimensions: cultural, medium 62.5% (55), high 34.1% (30), low 3.4% (1); social, medium 63.7% (56), high 29.5% (26), low 6.8% (6); personal, medium 50.0% (44), high 48.9% (43), low 1.1% (1); psychological, high 67.0% (59) and medium 33.0% (29). It is concluded that sensory MKT is significantly related to purchasing behavior (p=0.000), as well as in the following dimensions: olfactory (R= 0.395), auditory (R=0.395) and visual (R=0.313); while in the gustatory (R=0.182) and tactile (R=0.158) there is no significant relationship.